Answer:
D) (x,y) → (x+4, y-6)
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given that the points are X(2,3), Y(5,6), and Z(8,6)
The vertical translation down 'd' units then transformed to
(x,y) → (x, y-d)
The vertical translation down '6' units then transformed to
(x,y) → (x, y-6)
X(2,3)→ X¹( 2, 3-6)
Y(5,6)→Y¹(5,6-6)
Z(8,6)→Z¹(8,6-6)
Again
The Horizontal translation 'c' units right then transformed to
(x,y) → (x+C, y-d)
The Horizontal translation '4' units right then transformed to
(x,y) → (x+4, y-6)
The new co-ordinates
X(2,3)→ X¹( 2+4, 3-6)→X¹(6,-3)
Y(5,6)→Y¹(5+4,6-6)→ Y¹(9,0)
Z(8,6)→Z¹(8+4,6-6)→Z¹(12,0)
<u><em>Final answer:-</em></u>
The new co-ordinates are
X¹(6,-3) ,Y¹(9,0), Z¹(12,0)